Employing physical distance in ranking image-search results. (1st January 2014) - Khasawneh, Natheer; Al-Hailat, Rami A.; Al-Hammouri, Ahmad T.
In this paper, we enhance web image searching by exploiting the physical distance between an image on the web page and the surrounding text. The rationale is that the closer a term word to an image is, the more strong the relation between that word and image is. The physical distance is measured between the exact positions of a term and an image inside a webpage as it appears when it is completely rendered by a web browser. We show that incorporating physical distance in the ranking process indeed reduces the number of irrelevant images in the returned search results.